Bandgap Engineering through Controlled Oxidation of Polythiophenes1. (21st January 2014) - Wei, Sujun; Xia, Jianlong; Dell, Emma J.; Jiang, Yivan; Song, Rui; Lee, Hyunbok; Rodenbough, Philip; Briseno, Alejandro L.; Campos, Luis M.
Abstract The use of Rozen's reagent (HOF⋅CH3CN) to convert polythiophenes to polymers containing thiophene‐1, 1‐dioxide (TDO) is described. The oxidation of polythiophenes can be controlled with this potent, yet orthogonal reagent under mild conditions. The oxidation of poly(3‐alkylthiophenes) proceeds at room temperature in a matter of minutes, introducing up to 60 % TDO moieties in the polymer backbone. The resulting polymers have a markedly low‐lying lowest unoccupied molecular orbital (LUMO), consequently exhibiting a small bandgap. This approach demonstrates that modulating the backbone electronic structure of well‐defined polymers, rather than varying the monomers, is an efficient means of tuning the electronic properties of conjugated polymers.